Subjective comparison on the ITS synthetic hazy dataset. - Xiaoxia Lin (9165920) (2025)
(a) Hazy image, (b) Ground Truth, (c) FFA [2], (d) GDN [3], (e) IA-YOLO [12], (f) Dehamer [5], (g) MSBDN [4], (h) Ours.